ANALISIS TINGKAT KESEHATAN PT BANK CENTRAL ASIA (BCA) SYARIAH DENGAN METODE CAMEL PERIODE 2019-2023 - Devina Damayanti Br Siahaan (MANAJEMEN, 2025)
Financial performance is the result of achieving the success of the bank's financial condition in a certain period to help investors in making investment decisions in a bank. The formulation of the problem in this study is how the health level of PT. Bank Central Asia Syariah is assessed from the aspects of capital, assets, management, earnings, and liquidity. The purpose of this study is to determine the health level of PT. Bank Central Asia (BCA) Syariah. The analysis tool used is CAMEL. The theory used in this study is a theory related to the CAMEL method. Assessment using the CAMEL method consists of CAR, PPAP, ROA, BOPO and FDR. The data used is financial report data obtained from the company PT. Bank Central Asia (BCA) Syariah 2019-2023 published through the website www.bcasyariah.co.id. This type of research is descriptive quantitative research, namely research that emphasizes testing theories through measuring research variables with numbers and conducting data analysis with statistical procedures. The data sources used are secondary data. The results of this study indicate that the level of bank health at PT. Bank Central Asia (BCA) Syariah is measured from financial performance. Capital is measured using the CAR ratio categorized in the HEALTHY group, assets are measured using the KAP ratio categorized in the HEALTHY group, Management is measured using the NPM categorized in the HEALTHY group, Earning is measured using the ROA ratio categorized in the HEALTHY group, and BOPO and liquidity are measured using the FDR ratio categorized in the HEALTHY group.